Effect of glucose concentration on peripheral nerve and its response to anoxia. Issue 3 (16th December 2013) - Stecker, Mark M.; Stevenson, Matthew
ABSTRACT Introduction: Glucose has a significant effect on nerve function. Methods: The effects of glucose on the nerve action potential (NAP) were investigated for concentrations between 0 and 55.5 mmol/L in an in vitro system using rat sciatic nerve. The effects of glucose were investigated in nerves exposed to oxygenated perfusate and those subjected to anoxia. Multiple aspects of the NAP were analyzed. Results: Hypoglycemia produces immediate reductions in NAP amplitude and velocity, whereas hyperglycemia has the opposite effect in the short term. Over a 12‐hour experiment, the amplitude of the NAP remained stable for glucose concentrations in the range 2.8–5.6 mmol/L, but, when the glucose concentration was <2.8 mmol/L or >27.8 mmol/L, the amplitude of the NAP declined. The deleterious effects of hyperglycemia (≥27.8 mmol/L) or hypoglycemia (<4.2 mmol/L) were more pronounced in nerves exposed to intermittent anoxia. Conclusions: This findings confirm the importance of glucose concentration for nerve function especially during anoxia. Muscle Nerve49:370–377, 2014